Ruang Ketiga Pada Gerbang Rumah Peranakan, Pecinan, Lasem, Jawa Tengah, Indonesia Kajian Kes: Rumah Peranakan Kidang Mas - Darmayanti, Tessa Eka (2021)
The gateways to the Peranakan house in Lasem Chinatown are seen as an icon. However, maintaining the existence of these gates is a serious challenge due to the government's lack of attention and public understanding on historical and cultural values. Its manifestation is even more awful due to phenomena happened to the Peranakan house in Chinatown, Lasem, namely being abandoned, demolished, exploited, and overly decorated. This investigation aims to explore about the various "traits" in-depth through various activities at the Peranakan house gateway in the third room so that the philosophy is not lost and the identity is preserved. Space trialectic theory of Lefebvre-Soja provides a different perspective on the existence of the third room at the gate of the Peranakan house following the study on the Kidang Mas Peranakan house (RPKM). It is interpreted through the experiences of the residents and investigators based on the social and cultural aspects prevailing in the Lasem and Chinatown areas. The analysis was carried out using an ethnographic approach, made hand paintings reinforced by the concept of seven human senses following the phenomenological approach by Pallasmaa. Everything is described in detail using narrative methods related to the local social and cultural conditions. This study has finally made three investigative contributions. First is the methodological aspect, namely the merging of the Lefebvre-Soja space trialectic theory with the phenomenology-Pallasmaa principle by embracing hand painting and the concept of the seven human senses which reinforced the narrative thread.